RabGAP AS160/TBC1D4 deficiency increases long-chain fatty acid transport but has little additional effect on obesity and metabolic syndrome in ADMSCs-derived adipocytes of morbidly obese women - Mikłosz, Agnieszka; Łukaszuk, Bartłomiej; Supruniuk, Elżbieta; Grubczak, Kamil; Kusaczuk, Magdalena; Chabowski, Adrian (Frontiers in Molecular Biosciences, 2023)
The Akt substrate of 160 kDa (AS160), also known as TBC1 domain family member 4 (TBC1D4) represents a crucial regulator of insulin-stimulated glucose uptake in skeletal muscle and adipose tissue. Recent evidence suggests that AS160/TBC1D4 may also control long chain fatty acids (LCFAs) cellular entry, resulting in a change in the lipid profile of muscle and fat cells of lean subjects. However, there is virtually no data on AS160/TBC1D4 expression and its modulatory role in lipid metabolism in the adipocytes from morbidly obese individuals of different metabolic status. In this study, we evaluated the effect of the three main factors, i.e. AS160 silencing, obesity, and metabolic syndrome on the lipid uptake and profile in fully differentiated adipocytes derived from mesenchymal stem cells (ADMSCs) of lean and obese (with/without metabolic syndrome) postmenopausal women. Additionally, we tested possible interactions between the explanatory variables. In general, obesity translated into a greater content of fatty acid FA transporters (especially CD36/SR-B2 and SLC27A4/FATP4) as well as boosted accumulation of all the examined lipid fractions, i.e. triacylglycerols (TAG), diacylglycerols (DAG) and free fatty acids (FFA). The above was further enhanced by metabolic syndrome. Moreover, also AS160 deficiency increased the abundance of SLC27A4/FATP4 and CD36/SR-B2 especially on the cell surface of the adipocytes derived from ADMSCs of subcutaneous deposit. This was further accompanied by an increased LCFA (palmitic acid) uptake. Despite the above AS160 silencing seemed to be unable to significantly affect the phenotype of the adipocytes stemming from obese patients with respect to their cellular lipid profile as we observed virtually no changes in TAG, DAG and FFA content when compared to the cells with the reference level of the protein. Nevertheless, knockdown of AS160 stimulates fatty acid oxidation, which may indicate that adaptive mechanisms counteract excessive lipid accumulation. At the same time, adipocytes of visceral origin were rather insensitive to the applied intervention.